Successful clinical and virological outcomes of liver transplantation for HDV/HBV-related disease after long-term discontinuation of hepatitis B immunoglobulins - Lenci, Ilaria; Tariciotti, Laura; Angelico, Roberta; Milana, Martina; Signorello, Alessandro; Manzia, Tommaso Maria; Toti, Luca; Tisone, Giuseppe; Angelico, Mario; Baiocchi, Leonardo (Clinical Transplantation)
Background Indefinite, long-term administration of hepatitis B immunoglobulins (HBIg), together with a third generation nucleos(t)ide analog (NA), is the currently recommended prophylactic strategy to prevent viral recurrence after liver transplantation (LT) for Hepatitis Delta virus (HDV)/Hepatitis B virus (HBV)-related disease. Methods We retrospectively analyzed the safety and long-term clinical and virological outcomes of a consecutive cohort of 16 patients (10 males, median age 64.5, range 41–75) transplanted for HDV/HBV-related cirrhosis at our Institution, who discontinued HBIg after a median of 24.5 months (range 15–116) after transplant. All patients continued prophylaxis with same NA used before LT. Recurrence of HDV/HBV infection was defined as reappearance of serum HDV-RNA with detectable serum HBsAg and/or HBV-DNA. Results The median follow-up after LT was 138 months (range 73–316) and 110 months (range 52–200) after HBIg withdrawal. All patients were HBsAg-positive, HBV-DNA negative, and anti-HDV positive at the time of LT and without coinfections with HCV or HIV. Patients were followed with biochemical and virological tests every 3–6 months after HBIg withdrawal. No recurrences of HDV/HBV infection or disease were observed during monoprophylaxis with NA. In addition, eight patients (50%) spontaneously developed anti-HBs titers above 10 IU/L at a median of 74 months (range 58–140) following HBIG discontinuation. Conclusions HBIg withdrawal after LT is a safe and efficacious strategy in patients transplanted for HDV/HBV disease and is frequently associated with the spontaneous development of serological immunity against HBV. These data call for a revision of current prophylactic recommendations in this setting.
Keywords: hepatitis B virus; hepatitis D virus; immunoglobulins; liver transplantation; withdrawal

Liver transplantation from active COVID‐19 donors: A lifesaving opportunity worth grasping? - Romagnoli, Renato; Gruttadauria, Salvatore; Tisone, Giuseppe; Ettorre, Giuseppe Maria; Carlis, Luciano De; Martini, Silvia; Tandoi, Francesco; Trapani, Silvia; Saracco, Margherita; Luca, Angelo; Manzia, Tommaso Maria; Comandini, Ubaldo Visco; et al. (American Journal of Transplantation, 2021)
COVID‐19 pandemic dramatically impacted transplantation landscape. Scientific societies recommend against the use of donors with active SARS‐CoV‐2 infection. Italian Transplant Authority recommended to test recipients/donors for ...